Analisis Pengaruh Tingkat Pengangguran Terhadap Kemiskinan Melalui Pertumbuhan Ekonomi di Sumatera Utara - Haikal Dzikri Daulay; Siti Endang Sariniah; Zahra Audi Maharani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research is a process of analyzing the effect of unemployment on poverty through economic growth in North Sumatra Province from 2021 until 2023. The survey was conducted in 2023 districts/cities in North Sumatra Province by the North Sumatra Central Statistics Agency. 2021-2023. The results of this research state that population growth has a strong significance on the level of open unemployment. However, economic growth has a negative impact on the open unemployment rate. At the same time, population size and economic level are related to open unemployment. These results suggest that states and city governments should pay more attention to this issue. To improve the regional economy and slow population growth, apart from investing money, the focus should also be on creating new jobs. In this way, more people will get jobs and the problems of unemployment and poverty will be reduced.